Intervensi Gaya Hidup Terhadap Pencegahan Diabetes Melitus Tipe 2 Pada Pasien Pra Diabetes - Fitriani Fitriani; Sanghati Sanghati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Pre-diabetes is a condition where blood glucose levels are above normal, but do not meet the standard to be diagnosed as diabetes. This literature review aims to determine the effectiveness of lifestyle interventions in preventing the risk of developing type 2 diabetes in pre-diabetic patients. Methods: Search articles using five databases, namely Pubmed, Proquest, ScienceDirect, Cochrane Library and Google Scholar identified 21,380 articles. Results: Five studies that met the criteria showed that lifestyle interventions were effective in preventing the risk of developing type 2 diabetes in pre-diabetic patients. Four studies reported no participant developing type 2 DM and only one study reported progression of pre-diabetes to type 2 DM, but overall it was greater in the control group than in the treatment (22.8% vs 15.0%). At the age of 18-64 years, lifestyle interventions can reduce the risk of diabetes in two years by 30%, in the following years 40% and 10%, respectively. While at the age of 65-84 years from 40% to 50% in the first two years and from 10% to 20% in the following years. Conclusion: Based on the results of a review of five articles, it was concluded that lifestyle interventions can effectively prevent the risk of developing type 2 diabetes in pre-diabetic patients